Belt and Road Initiative: Prospects for Nepal-China Cooperation - Pandit, Kamal (Social Inquiry: Journal of Social Science Research, 2019)
Connectivity has always been a hindrance for landlocked countries to efficiently deliver their products and services across the globe. Such issue is no different in case of Nepal. Being a mountainous and landlocked country, Nepal is facing problems in trade, transportation and economic development. The introduction of the Belt and Road Initiatives by China to improve trade and connectivity among its member countries brings a new hope of economic prosperity. One can simply argue on the dark side of the project through media evidence illustrating the case of Hambantota Port, Sri Lanka. The purpose of the paper is to identify and formulate strategies for implementing the BRI projects in Nepal for enhancing economic development through connectivity. Paucity of academic discourse on the implementation strategies of the BRI project in Nepal was one of the motivating factors for this research. Literature review forms the major portion of research methodology and critical analysis has been done to derive conclusions. During the last 4 decades, China had an impressive achievement transforming itself from agricultural economy to world class digital powerhouse. It was found that from hardworking farmers, they have moved to become a traveller for pleasure and business. And now with its global development strategy involving infrastructure development and investment in more than 150 countries, it is at the edge of becoming the super power of the world. Nepal’s participation in the BRI goes beyond physical connectivity as we share history immemorial in terms of trade, religion, ideas and culture. The connectivity projects will definitely shape the trade of Nepal through exposure and efficient custom and transit transport procedures overcoming the problems in trade, transportation and economic development.